Convenience as a Key Driver in Extending the Cumulative Lifespan of Furniture - Nguyen, Anna Kieu; Christiansen, Clara Olivia Birkekær; Therkelsen, Frida Elmstrøm; Hansen, Andreas Kornmaaler (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
In response to environmental challenges and overconsumption, design strategies focusing on product longevity have emerged. While product longevity is partly determined by physical durability, it is also heavily influenced by the consumer. Therefore, understanding consumer attitudes toward product lifespans is essential for gaining insights into longevity. Specifically, this study investigates how consumers’ valuation of furniture impacts its lifespan. The findings are based on data from semi-structured interviews and a survey provided by AAU Design Lab, analyzed through reflexive thematic analysis. The study introduces two terms to further specify the understanding of product lifespan: individual ownership lifespan and cumulative lifespan. The study found that emotional attachment is not necessarily essential for achieving prolonged cumulative lifespan of furniture, challenging existing strategies like design for attachment and emotional durability. While these strategies influence individual ownership lifespan, the findings in this paper suggest that convenience is the key driver in extending the cumulative lifespan of furniture by enabling its reuse through accessible disposal methods and platforms. Accordingly, putting a stronger focus on the systems and contexts in which products exist could play an important role in extending their lifetime. As this is a preliminary study with limited data, these findings should be considered an interesting starting point for further investigation.